Bidirectional shunt in uncomplicated atrial septal defect. Issue 5 (May 1984) - Galve, E; Angel, J; Evangelista, A; Anivarro, I; Permanyer-Miralda, G; Soler-Soler, J
Abstract : The presence of right to left shunts at atrial level in 40 patients with an uncomplicated atrial septal defect was determined by measuring the pulmonary vein to systemic artery oxygen stepdown . In six patients (group 1) a sizeable right to left shunt was found: left atrial oxygen stepdown was greater than or equal to 0.7 vol%, mean right to left shunt 0.67 1/min/m2 (range 0.36-1.0), and arterial oxygen saturation between 84% and 90.5%. The patients in group 1 did not show any differences from those with left to right shunts alone (group 2) as regards sex, cardiac rhythm, heart rate, "a" wave and mean right atrial pressure, end diastolic right ventricular pressure, morphology of diastolic right ventricular pressure curves, pulmonary to systemic vascular resistance ratio, size of the defect, and coexistence of anomalous pulmonary venous drainage. Patients with coexisting right to left shunts were, however, significantly older and had smaller left to right shunts. Thus an appreciable number of patients with uncomplicated atrial septal defects have major right to left shunts which are unrelated to pulmonary hypertension or right heart failure. These shunts may be detected by the usual oximetric techniques and apparently develop with age, which suggests that they result from changes associated with chronic right volume overload.